Regulation of a Protein Acetyltransferase in Myxococcus xanthus by the Coenzyme NADP(+) - Liu, Xin-Xin (J Bacteriol, 2016)
NADP(+) is a vital cofactor involved in a wide variety of activities, such as redox potential and cell death. Here, we show that NADP(+) negatively regulates an acetyltransferase from Myxococcus xanthus, Mxan_3215 (MxKat), at physiologic concentrations. MxKat possesses an NAD(P)-binding domain fused to the Gcn5-type N-acetyltransferase (GNAT) domain. We used isothermal titration calorimetry (ITC) and a coupled enzyme assay to show that NADP(+) bound to MxKat and that the binding had strong effects on enzyme activity. The Gly11 residue of MxKat was confirmed to play an important role in NADP(+) binding using site-directed mutagenesis and circular dichroism spectrometry. In addition, using mass spectrometry, site-directed mutagenesis, and a coupling enzymatic assay, we demonstrated that MxKat acetylates acetyl coenzyme A (acetyl-CoA) synthetase (Mxan_2570) at Lys622 in response to changes in NADP(+) concentration. Collectively, our results uncovered a mechanism of protein acetyltransferase regulation by the coenzyme NADP(+) at physiological concentrations, suggesting a novel signaling pathway for the regulation of cellular protein acetylation. IMPORTANCE Microorganisms have developed various protein posttranslational modifications (PTMs), which enable cells to respond quickly to changes in the intracellular and extracellular milieus. This work provides the first biochemical characterization of a protein acetyltransferase (MxKat) that contains a fusion between a GNAT domain and NADP(+)-binding domain with Rossmann folds, and it demonstrates a novel signaling pathway for regulating cellular protein acetylation in M. xanthus. We found that NADP(+) specifically binds to the Rossmann fold of MxKat and negatively regulates its acetyltransferase activity. This finding provides novel insight for connecting cellular metabolic status (NADP(+) metabolism) with levels of protein acetylation, and it extends our understanding of the regulatory mechanisms underlying PTMs.